非局限期结外鼻型NK/T细胞淋巴瘤患者的临床预后及EBV-DNA在疗效监测及预后评估中的意义 (Zhonghua Xue Ye Xue Za Zhi, 2020)
OBJECTIVE: This study aimed to explore the clinical characteristics, survival rate, and prognostic factors of advanced-stage extranodal nasal type NK/T cell lymphoma (ENKTL) patients. METHODS: The clinical data of 51 advanced-stage ENKTL patients in Peking Union Medical College Hospital from January 2012 to September 2019 were retrospectively analyzed. The clinical characteristics, treatment responses, survival rate, and prognostic factors were elucidated. The differences between nasal and non-nasal type and the significance of EBV-DNA in treatment response assessment and prognosis analysis were also evaluated. RESULTS: The male-to-female ratio in the whole group was 2.9∶1 with a median age of 42 years old (range, 14–67 years). The median follow-up time was 30 months (range, 1–78 months). The one- and three-year progression-free survival (PFS) rates for the whole cohort were 34.1% and 24.6%, respectively, and the one- and three-year overall survival (OS) rates were 39.9% and 26.6%, respectively. The ratio of nasal to non-nasal type was 1.6∶1. The proportion of hemophagocytic lymphohistiocytosis (HLH) was significantly higher in non-nasal-type patients than nasal-type (P=0.039), and the complete response (CR) rate of first-line chemotherapy is significantly lower in non-nasal type patients (P=0.008). The median OS for nasal and non-nasal types were nine months and four months, respectively. The three-year PFS rates of nasal and non-nasal type patients were 36.0% and 10.0% (P=0.029), respectively, and the three-year OS rates were 37.9% and 11.4% (P=0.050), respectively. The correlation between the Epstein-Barr virus DNA (EBV-DNA) and treatment response were satisfactory. Survival curve between baseline EBV-DNA-negative and EBV-DNA-positive patients showed no significant difference. The three-year OS rates of EBV-DNA-negative and EBV-DNA-positive patients after one cycle of treatment were 77.9% and 8.1% (P=0.002), respectively. In a multivariate analysis, EBV-DNA-positive following one cycle of treatment was an independent adverse prognostic factor for OS. CONCLUSION: The efficacy of pegaspargase-based chemotherapy and long-term survival of advanced-stage ENKTL patients were still poor. Clinical characteristics, treatment response, and long-term survival of non-nasal-type patients were worse than that of nasal-type patients. In a multivariate analysis, EBV-DNA-positive after one cycle of treatment was an independent adverse prognostic factor for OS. It can be used for early prediction of treatment response and prognosis.